MACROSCOPICS AND MICROSCOPICS FEATURE OF WITAR RATS LIVER AFTER IMMERSION IN GRADUAL CONCENTRATION OF RANDU HONEY - Putri Ariani Kusuma; Tuntas Dhanardhono; Saebani Saebani; Ratna Damma Purnawati; Hermawan Istiadi (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background Formaldeyde is main substance used for organ embalming and even for foods preservations. However, long and high exposure of formaldeyhde lead to various organs irritations. Honey is well-known for its natural preservative activity expected to be the soultion for the problem so there is safe alternative for organ preservations.Aim Observation and examintaion the difference of macroscopic and microscopics feature of Wistar rats liver after immersion of formaldehyde and randu honey.Methods Experimental with post-test only control group design using 24 male Wistar rats as sample, randomly divided into 4 groups consist of: Group C (preserved with 10% formaldehyde solutions), P1 (preserved with 10% randu honey solutions), P2 (preserved with 20% randu honey solutions) and P3 (preserved with 30% randu honey solutions). The sampels were preserved for 24 hours then macroscopic (smell,color and size) and microscopic study with Hematoxylin-Eosin (HE) stain using 400x observation performed. Manja Roenigk score were used to accessed the degree of live microsopic damage.Results There are normal cells, mild damage, moderate damage and severe damage respectively in the group C: 36%,47%,17%,0% ; P1: 0%,27%,46%,27% ; P2: 0%,77%,17%,6% ; P3: 47%,33%,17%,3%. Kruskal-Wallis test showed significant results with p=0.000. With Mann-Whitney test, significant results were found between group C with P1 (0.000), C with P2 (0.006), P1 with P2 (0.000), P1 with P3 (0.000) and P2 with P3 (0.003). However, test result were not significant berween group C with P3 (0.684).Conclusions There were differences in macroscopics and microscopic features between Wistar rats liver after immersion in formaldehyde and randu honey. The best features showed in samples preserved in 30% Randu Honey solutions.